Imágenes y optimismos - Arancibia, Victor (Oficios Terrestres, 2016)
In Latin America, the update of the right has chosen for the speech of the optimism alongside it produces a depletion of rights policies and an evident persecution of the actors who took them forward. The central question of this article is to decipher how these processes occurred presented as unnoticeable, sometimes denied and other strategically hidden social visibility and at the same time, achieve an important acceptability in modern democracies in modern democracies through the recovery of old demands that consolidate zócalos of the perception and generate new colonialism.